The electrical transport properties and Hall effect measurements on a (TBCCO) superconductor - Cavdar, S; Yakuphanoğlu, Fahrettin; Koralay, H; Günen, A (Elsevier Science Bv, 2006)
The electrical resistivity and thermal conductivity of TBCCO sample have been investigated as a function of temperature and magnetic field up to 1.2 T. Magnetic field strongly affects the superconducting transition shifting T-c towards lower temperatures. The change of the normal resistivity is very small with the magnetic field. The experimental data of electrical resistivity is fitted to the thermally activated flux flow (TAFF) model. It is observed that the flux-pinning activation energy decreases with magnetic field, which is in agreement with other works. It is found that the Hall coefficient above T-c is positive and increase with increasing temperature. This suggests that the conduction above T-c can be explained with a single band model. The thermal conductivity of the sample decreases up to 120 K and afterwards tends a constant trend. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: superconducting; TBCCO; Hall effect; thermal conductivity